Comparison between linear and star-like HPMA conjugated pirarubicin (THP) in pharmacokinetics and antitumor activity in tumor bearing mice - Nakamura, Hideaki; Koziolová, Eva; Etrych, Tomáš; Chytil, Petr; Fang, Jun; Ulbrich, Karel; Maeda, Hiroshi (European journal of pharmaceutics and biopharmaceutics, 2015)
Previously we showed that linear poly(N-(2-hydroxypropyl)methacrylamide) conjugates of pirarubicin (THP), LP-THP, with MW about 39 kDa, exhibited far better tumor accumulation and therapeutic effect than that of parental free THP. To improve the pharmacokinetics of LP-THP further, high-MW conjugate of poly(amido amine) (PAMAM) dendrimer grafted with semitelechelic HPMA copolymer (PHPMA) was synthesized [star polymer (SP); 400 kDa] and conjugated with THP via hydrazone bond-containing spacer (SP-THP). THP was conjugated to SP to form SP-THP via acid cleavable hydrazone bonding, which responds to acidic milieu of tumor tissue. As a consequence, it would release free THP, by active therapeutic principle. SP-THP exhibits larger hydrodynamic diameter (25.9 nm) in aqueous solution than that of LP-THP (8.2 nm) as observed by light scattering and size exclusion chromatography. Because of the larger size, the tumor AUC5h-72 h of SP-THP was 3.3 times higher than that of LP-THP. More importantly, released free THP was retained selectively in the tumor tissue for at least up to 72 h after administration of SP-THP. We found that SP-THP exhibited superior antitumor effect to LP-THP against both S-180 tumor-bearing mice in vivo, and with chemically AOM/DSS-induced colon tumor-bearing mice, most probably due to their different molecular size. In our comparison study of in vitro and in vivo behavior of SP-THP and LP-THP we concluded that SP-THP exhibited enhanced therapeutic efficacy not only in implanted tumor but also in orthotopic/spontaneous tumor despite its higher toxicity compared to LP-THP. Upon these findings further investigation using various tumors including transgenic, and metastatic tumors is going to be conducted soon.
Keywords: nosiče léků; Mice, Inbred ICR; Drug Carriers; melanom experimentální; nádorové buněčné linie; Doxorubicin; berberinové alkaloidy; methakryláty; HeLa Cells; mužské pohlaví; Methacrylates; Mice; Cell Line, Tumor; Dendrimers; Antineoplastic Agents; Berberine Alkaloids; Neoplasms; Polymers; dendrimery; doxorubicin; protinádorové látky; zvířata; Humans; myši inbrední ICR; nádory; Melanoma, Experimental; myši; polymery; HeLa buňky; lidé; Male; Animals